Classroom-oriented research: Processing Instruction (findings and implications). (July 2019) - Benati, Alessandro
Abstract : This paper firstly presents and examines the pedagogical intervention called Processing Instruction (PI). Secondly, it reviews and discusses the main findings of the empirical research conducted to measure the relative effects of PI. Current research trends within the PI research framework will be outlined. Experimental research investigating the effects of this pedagogical intervention in language teaching, and grammar instruction in particular, has primarily used listening and reading measures (so-called 'off-line measures') to elicit how learners comprehend and process sentences. On-line measurements, such as eye tracking and self-paced reading, have now been incorporated into PI research to measure language processing more directly. Finally, this paper provides specific guidelines and procedures for teachers on when and how to use PI.